2013
DOI: 10.3957/056.043.0110
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium Levels in Liver, Kidney and Muscle of Harvested Wild Springbok (Antidorcus marsupialis) Under Extensive Management in Southern and Southeastern Namibia

Abstract: Of all animal tissues, livers and kidney constitute a special dilemma in that they have a tendency to bioaccumulate toxic metals such as arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg). Maximum concentrations (ML) for Hg, Pb, Cd and tin (Sn), but not As in foodstuffs are set by European Commission Regulations. The aims of this study were 1) to determine the concentrations of As, Cd, Pb and Hg in the livers and kidneys of nine cows from the index farm and 2) to combine the kidney Cd results from these 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
2
3
1
Order By: Relevance
“…The significantly high levels reported in this finding for both the exposed and the suspected unexposed groups were similar to report of manifold elevated cadmium levels in muscle and edible offal slaughtered in Nigeria above the FAO/WHO maximum level (Ihedioha and Okoye, 2012;Adetunji, Famakin and Chen, 2014). This is however contrary to previous reports in which the levels of cadmium reported in tissues of meat slaughtered in Nigeria (Bala et al, 2012) and other places were below the maximum level (Jorhem et al, 1991;Miranda et al, 2001;Magwedere et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The significantly high levels reported in this finding for both the exposed and the suspected unexposed groups were similar to report of manifold elevated cadmium levels in muscle and edible offal slaughtered in Nigeria above the FAO/WHO maximum level (Ihedioha and Okoye, 2012;Adetunji, Famakin and Chen, 2014). This is however contrary to previous reports in which the levels of cadmium reported in tissues of meat slaughtered in Nigeria (Bala et al, 2012) and other places were below the maximum level (Jorhem et al, 1991;Miranda et al, 2001;Magwedere et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Our report of elevated tissue lead levels was found to be highest in the liver in the exposed group compared to the kidney and muscle. This report is similar to previous studies in which the mean lead concentration was found to be highest in the liver (Swaileh et al, 2009;Ihedioha and Okoye, 2012;Magwedere et al, 2013) compared to the kidney as reported by other studies (Liu, 2003;Adetunji, Famakin and Chen, 2014). The observation of high lead levels in both the kidney and the liver however is consistent with the relevance of these organs as important site of metal accumulation due to their role as portal of metabolism and excretion (Liu, 2003;Serpe et al, 2012;Akoto et al, 2014) and their total rank score (TRS) based on their ability to concentrate metals (Swaileh, Hussein and Abu-Elhaj, 2003;Swaileh et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been found that, in general, [Pb] is lower in predators than their prey, since rapid excretion occurs and absorption of metals across the gut tends to be incomplete (Fowler, 1982;Luoma, 1983;Szefer, 1991). Studies on the distribution of heavy metals in the body tissues of an antelope, Springbok (Antidorcas marsupialis), showed 97% of liver samples, 59% of kidney samples and all muscle samples to be below the detection limit (Magwedere et al, 2013). Whitebacked Vultures mostly feed on muscle and viscera, generally ignoring the skin and bones (Piper, 2005a) and even though they may consume the former tissues in large quantities, the negligible contribution of biomagnification could not account for their elevated and, in some cases, extreme blood [Pb].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some bullets contain traces of lead (Pb) and other heavy metals which may contaminate the wildlife carcasses or the environment during hunting. We have reported that some liver samples from free-ranging springbok slaughtered for consumption had Pb concentrations above the accepted limit, implying a potential chemical risk to humans (Magwedere et al ., 2013c ). Therefore, the development of a new regulatory framework catering for game meat should take into consideration these potential factors which may impinge on current limits of biological and chemical hazards.…”
Section: Introductionmentioning
confidence: 99%